2007
DOI: 10.2131/jts.32.143
|View full text |Cite
|
Sign up to set email alerts
|

Kojic Acid -Absence of Tumor-Initiating Activity in Rat Liver, and of Carcinogenic and Photo-Genotoxic Potential in Mouse Skin

Abstract: -Kojic acid (KA) has been widely used as a quasi-drug ingredient. Possible promotion activity of KA was suggested on livers of mouse and rat by findings obtained in genotoxicity and carcinogenicity studies performed thus far. Therefore, in order to examine safety as a quasi-drug ingredient, we investigated the presence of initiation activity in rat liver and the photo-genotoxicity and carcinogenicity in mouse skin. In medium-term carcinogenesis test in rats, 2.0% KA was orally given to F344/ DuCrj rats for 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Moreover, these hydroxypyrone derivatives are known as effective chelating agents forming complexes with metals 5,12,13 and this ability plays a significant role in antimicrobial activity 14 . Kojic acid and its derivatives also display a variety of biological activities, such as antiepileptic 4,[6][7][8][9] , modest anti-inflammatory agent 5 , food additive 15 , antioxidant or antibrowning agent 16 , skinlightening product in cosmetics as a result of inhibition of melanin production 17 , herbicidal 18 , anti-speck 19 , pesticide and insecticide 20 , antitumor activity 21 and anti-diabetic agent 22 . Epilepsy, one of the more common neurological disorders, affects a large section of people.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these hydroxypyrone derivatives are known as effective chelating agents forming complexes with metals 5,12,13 and this ability plays a significant role in antimicrobial activity 14 . Kojic acid and its derivatives also display a variety of biological activities, such as antiepileptic 4,[6][7][8][9] , modest anti-inflammatory agent 5 , food additive 15 , antioxidant or antibrowning agent 16 , skinlightening product in cosmetics as a result of inhibition of melanin production 17 , herbicidal 18 , anti-speck 19 , pesticide and insecticide 20 , antitumor activity 21 and anti-diabetic agent 22 . Epilepsy, one of the more common neurological disorders, affects a large section of people.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 KA 30 and its derivatives have been used in a variety of medical, food, agricultural, and industrial applications, such as an antibrowning agent (antispeck) and antioxidant; [31][32][33] for skin care, antiacne, and cosmetic applications due to its potent skin lightening/depigmenting properties, [34][35][36][37] and used for herbicide, insecticide, pesticide, [38][39][40][41] antidiabetic, 42 antitumor, 43 antiproliferative, 44 anticonvulsant, 31 and antimicrobial (including both antibacterial and antifungal) activities. 29,[45][46][47][48] In addition, it has also been shown that KA significantly enhances neutrophil phagocytosis and lymphocyte proliferation.…”
mentioning
confidence: 99%
“…It has been previously reported that skin nodules developed in CD-1 (ICR) mice treated with DMBA. 4,5 In that bioassay, TPA was applied at 4 mg/200 mL twice a week for 19 weeks, and the multiplicity ranged from 12 to 28. 4,5,21 In the present study, DMBA used as initiator was applied to back skin at a dose of 50 mg/100 mL acetone, and this dose was half that used in the 2-stage skin carcinogenesis bioassay with CD-1 (ICR) mice.…”
Section: Discussionmentioning
confidence: 99%